Taxonomia e distribuição do gênero Isotomiella Bagnall, 1939 (Collembola, Isotomidae) na Floresta da Tijuca, Rio de Janeiro, RJ, Brasil - Mendonça, Maria Cleide de (2002)
The taxonomy and ecology of the fauna of Isotomiella Bagnall, 1939 was studied in four areas at Floresta da Tijuca, from August/ 1999 to July /2000. Twenty-four monthly collections were made in litter and soil, totaling about 18.000 springtails, from which 3.552 belong to the genus Isotomiella. Morphological studies enabled the description of 25 species, 15 of them new to science. The distribution of 6 taxa was enlarged. A representative picture of the most abundant, frequent and characteristic species of each substratum was also obtained. The largest diversity and equitability of species happened at "Barracão" station and, the largest richness, at "Bom Retiro" station. Both the correspondence analysis and the multiple regression showed that the most important elements in the spatial and temporal distribution were the humidity and the temperature of the substratum and the monthly minimum temperature.